Analysis of taxation and framework conditions for hybrid power plants consisting of battery storage and power-to-heat providing frequency containment reserve in selected European countries. (November 2021) - Worschech, Alena; Schlachter, Uli; Wigger, Henning; Hanke, Benedikt; Draheim, Patrick; Schuldt, Frank; Brand, Urte; Diekmann, Theys; Vogt, Thomas; von Maydell, Karsten
Abstract: Flexible energy plants are one of the key requirements for future energy systems with high levels of fluctuating renewable energy. In the course of the transition to sustainable energy systems, regulatory frameworks and tax systems should promote carbon-reduced flexible power plants in a timely manner. This paper considers hybrid systems consisting of battery energy storage systems (BESS) and Power-to-Heat (PtH) modules which can contribute to a more flexible energy system by providing Frequency Containment Reserve (FCR). Contrary to many papers, this contribution explicitly focuses on taxes for FCR providing power plants, which are incurred annually or based on energy consumption. Additionally, regulatory frameworks are investigated, meaning requirements for FCR provision and conditions for energy trading. The effects of these factors on the economic efficiency of hybrid power plants providing FCR are analysed. The regulatory framework conditions and tax systems from three countries are analysed: Germany, France and Austria. For each of these countries four scenarios are simulated in which the net present values (NPV) are calculated considering the corresponding national tax systems and framework conditions. Additionally, operational strategies using the degrees of freedom (DoF) are examined regarding their influence on the economic performance. The comparison shows a huge influence of taxes on the profitability of the hybrid system. Framework conditions mostly play a minor role in this context. Compared to a benchmark scenario with uniform framework conditions and without taxes, on average the NPV decreases more rapidly considering taxes (−107 k€ in France to −710 k€ in Austria) than considering country specific framework conditions (−122 k€ in France to −308 k€ in Austria). Since framework conditions mostly determine the size of the battery capacity, they primarily affect the investment costs. Additionally, the longer the time slices and the earlier the gate closure is, the more often the hybrid systems violate requirements for FCR provision. Highlights: Taxes and framework conditions for battery and Power-to-Heat are presented. Situation in Germany, France and Austria is presented and compared. Net Present Value method is employed to evaluate a hybrid power plant. Simulations with real values show that taxes have a significant impact on economic value.